2013
DOI: 10.1038/cr.2013.158
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of MPZL1/PZR promotes tumor cell migration through Src-mediated phosphorylation of cortactin in hepatocellular carcinoma

Abstract: We have previously identified 1 241 regions of somatic copy number alterations (CNAs) in hepatocellular carcinoma (HCC). In the present study, we found that a novel recurrent focal amplicon, 1q24.1-24.2, targets the MPZL1 gene in HCC. Notably, there is a positive correlation between the expression levels of MPZL1 and intrahepatic metastasis of the HCC specimens. MPZL1 can significantly enhance the migratory and metastatic potential of the HCC cells. Moreover, we found that one of the mechanisms by which MPZL1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 61 publications
3
57
0
Order By: Relevance
“…A total of 144 somatic mutations were identified in the six HB tumors, including 28 somatic nonsynonymous mutations (Supporting Table S2). An average of 4.67 somatic mutations (range, 2‐8 mutations) were observed in each case, which is similar to the report of a recent meeting abstract in which 3.7 mutations per tumor were observed in 24 HB patients . Subsequently, 24 of the 28 nonsynonymous mutations (85.7%) within 21 genes were further verified in the same samples by Sanger sequencing (Fig.…”
Section: Resultssupporting
confidence: 85%
“…A total of 144 somatic mutations were identified in the six HB tumors, including 28 somatic nonsynonymous mutations (Supporting Table S2). An average of 4.67 somatic mutations (range, 2‐8 mutations) were observed in each case, which is similar to the report of a recent meeting abstract in which 3.7 mutations per tumor were observed in 24 HB patients . Subsequently, 24 of the 28 nonsynonymous mutations (85.7%) within 21 genes were further verified in the same samples by Sanger sequencing (Fig.…”
Section: Resultssupporting
confidence: 85%
“…In addition, using an integrated analysis of copy number and expression profiling data, one recent study found that the recurrent region of the 1q24.1-24.2 amplicon specifically targets the myelin protein zero-like protein 1 ( MPZL1 ) gene in HCC; the expression levels of MPZL1 were positively correlated with the intrahepatic metastasis of the HCC specimens[45]. …”
Section: Genomic Instabilitymentioning
confidence: 99%
“…More specifically, 8q24.21-24.22 is the most frequently amplified region in chromosome 8q, with amplification occurring in 53.4% of samples and targeting the known oncogenes myelocytomatosis viral oncogene ( MYC ), Arf-GAP with SH3 domain, ANK repeat and PH domain-containing protein 1 ( DDEF1 ), and human melanoma-derived leucine zipper extra-nuclear factor ( MLZE )[45]. MYC has been identified as a central regulator of malignant transformations in early hepatocarcinogenesis[46], and c-myc gene amplification has also been found to be significantly correlated with DFS and OS in patients with HCC after surgical resection[47].…”
Section: Genomic Instabilitymentioning
confidence: 99%
“…The tissues were formalin-fixed and paraffin-embedded for further immunohistochemistry. In this study, the criteria to define intrahepatic metastasis were: (1) tumors obviously growing from PVTT, (2) multiple satellite nodules which are smaller than the main tumor they surround, and (3) small single tumor which is present near the main tumor with similar histology 17, 18. The study protocol was approved by the research ethics committee of Sun Yat-Sen University.…”
Section: Methodsmentioning
confidence: 99%